2022
DOI: 10.1155/2022/1818758
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Induced Apoptosis, DNA Damage, and Oxidative Stress in Spinal Cord Neurons by Upregulating LPA4/LPA6 Receptors

Abstract: Lysophosphatidic acid (LPA) has disruptive effects on lumbar spinal stenosis (LSS). Recently, LPA has been reported to be involved in spinal cord neuronal injury and toxicity, promoting the pathogenesis of LSS. However, the exact effects of LPA on spinal cord neurons remain unknown. The purpose of this study is to investigate the effects of LPA (18 : 1) on spinal cord neuronal cytotoxicity, apoptosis, DNA damage, and oxidative stress. After clinical detection of LPA secretion, spinal cord neurons were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Growing evidence suggests that autophagy may maintain nuclear genomic integrity after SCI (Handa et al, 2020;Su et al, 2016;Tang et al, 2014;Taylor et al, 2022;Wang et al, 2018;Zhao et al, 2016). SCI has been shown to induce neuron DNA damage (Taylor et al, 2022;Yang et al, 2022). As expected, here we demonstrated that SCI damages neuron DNA and nuclear genomic integrity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Growing evidence suggests that autophagy may maintain nuclear genomic integrity after SCI (Handa et al, 2020;Su et al, 2016;Tang et al, 2014;Taylor et al, 2022;Wang et al, 2018;Zhao et al, 2016). SCI has been shown to induce neuron DNA damage (Taylor et al, 2022;Yang et al, 2022). As expected, here we demonstrated that SCI damages neuron DNA and nuclear genomic integrity.…”
Section: Discussionsupporting
confidence: 88%
“…SCI has been shown to induce neuron DNA damage (Taylor et al, 2022; Yang et al, 2022). As expected, here we demonstrated that SCI damages neuron DNA and nuclear genomic integrity.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by a secondary injury cascade that develops over the subsequent weeks and/or months. This involves vascular dysfunction ( 5 ), ischemia ( 6 ), excitotoxicity ( 7 ), ionic dysregulation ( 8 ), oxidative stress ( 9 ), neurotransmitter toxicity ( 10 ), lipid peroxidation ( 11 ), necrosis/apoptosis ( 12 ), immune-inflammatory response ( 13 ), and Wallerian degeneration and scar formation ( 14 ). These biological responses in secondary injury cause further damage to the spinal cord.…”
Section: Introductionmentioning
confidence: 99%